Pink Floyd The Wall - Waters, Roger 1943-; Gilmour, David 1946-; Guthrie, James 1953- (Sony Music Entertainment Inc., 1999)
"Grell-monströse Illustrationen zum gleichnamigen Rock-Oratorium der englischen Popgruppe "Pink Floyd": Ein Rockmusiker durchlebt in einem Hotelzimmer in Los Angeles Stationen seiner tristen Kindheit, seines gescheiterten Privatlebens und seiner steilen Karriere. Die visionären Fragmente seines Deliriums fügen sich zu einer Mauer, die ihn in völliger Kommunikationsunfähigkeit einschließt. [...]" [filmdienst.de]
Original: Großbritannien 1982
Deluxe DVD edition featuring: new Hi-Definition film transfer from the original wide screen interpositive ; previously unreleased film footage ; remasterd 5.1 Dolby Digital and Surround Encoded PCM Stereo Soundtracks from the original master tapes ; The other side of the wall - a 25 minute documentary about the making of the film ; running commentary from Roger Waters and Gerald Scarfe ; Retrospective - a new 45 min documentary with interviews with Roger Waters, Gerald Scarfe, Alan Parker, Peter Biziou, Alan Marshall and James Guthrie ; original film trailer and production stills ; newly designed interactive menues ; subtitles, scene/song selection, and secret buttons ; technical Sound System Set Up Guide
Keywords: Waters, Roger -- 1943- -- The wall; Insanity (Law) -- Drama; Rock musicians -- Drama; Dreharbeit; Bildplatte; Film; Interview; DVD-Video; Feature films; Music videos; Musical films